Reforms in Dars-e-Nizami Curricula: Western and Indigenous Influence During the 20th Century - Pakeeza Tabbasum; Ume Farva; Uzma Ehsan (Social Science Review Archives, 2025)
In the 20th century, educationists and researchers witnessed significant reforms in the Dars-e-Nizami curricula across South Asia, influenced by Western ideas and indigenous reform movements within religious communities. This article examines the evolution of Dars-e-Nizami education, focusing on the contrasting responses of Hindu and Muslim reformers to Western education and its impact on religious and social ideologies. This study utilises a qualitative research methodology, specifically employing discourse analysis, drawing on a comprehensive review of historical documents, academic journals, books, and other scholarly works. Key movements, such as the Deobandi and Aligarh movements, were analysed to understand their roles in modern Islamic education amidst global transformations Moreover, this article also examines how these reform movements shaped the evolution of Dars-e-Nizami curricula, highlighting the tensions between traditionalism and modernity, Indigenous and Western influences, and their implications for religious identity and education in South Asia. Future researchers should explore the socio-economic impact of the shift in madrasa education towards religious instruction and investigate the structural challenges in implementing effective reforms, focusing on creating a cohesive framework that aligns with broader educational goals.